Sensing DNA through DNA Charge Transport - Zwang, Theodore J. (ACS Chem Biol, 2018)
DNA charge transport chemistry involves the migration of charge over long molecular distances through the aromatic base pair stack within the DNA helix. This migration depends upon the intimate coupling of bases stacked one with another, and hence any perturbation in that stacking, through base modifications or protein binding, can be sensed electrically. In this review, we describe the many ways DNA charge transport chemistry has been utilized to sense changes in DNA, including the presence of lesions, mismatches, DNA-binding proteins, protein activity, and even reactions under weak magnetic fields. Charge transport chemistry is remarkable in its ability to sense the integrity of DNA.